Inventarisasi dan Pola Penyebaran Regenerasi Alami Semai Mangrove Sejati Di Utara Indonesia - Syahrial, Syahrial; Syahrian, Windi; Heriyanto, Teguh (Jurnal Perikanan dan Kelautan, 2018)
Increasing human activity in various sectors will contribute a pressure on mangrove ecosystems and cause of decreasing to mangrove species and it’s area. The inventory study and patterns of natural regeneration of mangrove seedling especially true man-grove in Northern Indonesia had been conducted in September 2015. It aimed to record the biodiversity in Indonesia and to know the shape of its distribution pattern. Collecting data of mangrove vegetation condition was done by transect line and plot. The line transect was drawn from the reference point (the outer mangrove stand) with the direction perpendicular to the coastline to the mainland and made plots according to the category. The results showed that mangrove vegetation in northern Indonesia found 4 species of natural seedlings, Lumnitzera littorea, Bruguiera cylindrica, Rhi-zophora stylosa and Xylocarpus moluccensis, those belonging to 3 families (Combretaceae, Rhizophoraceae and Meliaceae), in Station 1 dominated by seedlings B. cylindrica (62 individuals) and Station 2 dominated by X. moluccensis seedlings (8 individuals). Then the result of Morisita Index calculation showed that the distribution pattern of L. littorea, B. cylindrica and R. stylosa seedlings is classified regularly, while the distribution pattern of X. moluccensis seedling is clumped.